2004
DOI: 10.1207/s15374424jccp3301_14
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Depression in Youth: Relation Between the Children's Depression Inventory and a Structured Interview

Abstract: This study examined the utility of the Children's Depression Inventory (CDI) for predicting a diagnosis of a depressive disorder derived from the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders (4th ed. [DSM-IV], American Psychiatric Association, 1994) Child Edition (KID-SCID). The participants were 80 referred children and adolescents with a mean age of 12.21 years (range = 8 to 18 years). A categorical approach by means of a receiver-operating characteristics (ROC) ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
191
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(195 citation statements)
references
References 28 publications
2
191
1
1
Order By: Relevance
“…The internal consistency of the CDI was measured in Wu et al’s study (2010); Cronbach’s α was .88 for the total CDI and ranged from .60 to .74 for the subscales. Timbremont, Braet, and Dreessen (2004) suggested that a cut-off score of 19 was adequate for the general screening of depression (Timbremont et al, 2004). The internal consistency (Cronbach’s α) of the CDI in this study was .88 at T1, .89 at T2, .91 at T3 and .91 at T4.…”
Section: Methodsmentioning
confidence: 99%
“…The internal consistency of the CDI was measured in Wu et al’s study (2010); Cronbach’s α was .88 for the total CDI and ranged from .60 to .74 for the subscales. Timbremont, Braet, and Dreessen (2004) suggested that a cut-off score of 19 was adequate for the general screening of depression (Timbremont et al, 2004). The internal consistency (Cronbach’s α) of the CDI in this study was .88 at T1, .89 at T2, .91 at T3 and .91 at T4.…”
Section: Methodsmentioning
confidence: 99%
“…There were no ethnic or racial differences (White vs. nonWhite in one analysis, and White vs. African-American in a second analysis) in any of the variables (all t's<1.50).. Using the different recommended clinical cutoffs for the CDI revealed that 24.3% (CDI cutoff>19; Stark and Laurent 2001) or 32.3% (CDI cutoff>16; Timbremont et al 2004) of youth were above cut-scores for the CDI. Similarly, for the SDQ, 12.3% of youth were above cut-scores (Goodman 2001) for the internalizing scale and 15.1% for the conduct factor of the SDQ.…”
Section: Preliminary Analysesmentioning
confidence: 84%
“…A cutoff of 16 on the CDI was used to identify depressed participants. This cutoff score was found to maximize sensitivity and specificity of the CDI in identifying depressed adolescents in a study that used a standardized clinical interview as the gold standard (Timbremont et al 2004). Participants with analogue social phobia were identified using cutoff of 18 on the SPAI (March et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, convergent and discriminant validity have been established that indicate measurement equivalence in White and Black children (Cole et al 1998). The CDI has also been demonstrated to reliably identify children and adolescents with major depression and to differentiate children with major depression from those with an anxiety disorder or disruptive behavior disorder (Timbremont et al 2004). The item pertaining to suicidal ideation was removed from the measure at the request of school officials and the human subjects committee.…”
Section: Methodsmentioning
confidence: 99%